2018
DOI: 10.1371/journal.pone.0193288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysis membrane composition on plasma bisphenol A levels during online hemodiafiltration

Abstract: IntroductionBisphenol A (BPA) is an ubiquitous environmental toxin that is also found in dialyzers. Online hemodiafiltration (OL-HDF) more efficiently clears high molecular weight molecules, and this may improve BPA clearance. However, the BPA contents of dialysis membranes may be a source of BPA loading during OL-HDF.MethodsA prospective study assessed plasma BPA levels in OL-HDF patients using BPA-free (polynephron) or BPA-containing (polysulfone) dialyzers in a crossover design with two arms, after a run-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Although no effect was observed at lower BPA concentration, this finding is relevant because such concentration can usually be found in people whose jobs have high exposure to BPA, such as the plastics or thermal papers industry 25 – 27 . Furthermore, it has been shown that higher concentrations can be found in patients with kidney disease in advanced stages undergoing hemodialysis 44 , 45 , as well as in neonates undergoing surgical interventions where BPA levels can be even higher 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no effect was observed at lower BPA concentration, this finding is relevant because such concentration can usually be found in people whose jobs have high exposure to BPA, such as the plastics or thermal papers industry 25 – 27 . Furthermore, it has been shown that higher concentrations can be found in patients with kidney disease in advanced stages undergoing hemodialysis 44 , 45 , as well as in neonates undergoing surgical interventions where BPA levels can be even higher 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the general population has a concentration of BPA that ranges between 1 and 10 nM, while workers with high exposure to BPA can reach a concentration of 100 nM [73][74][75] . Furthermore, it has been described that surgical interventions or hemodialysis in the hospital environment can increase the exposure to BPA even more [44][45][46] .…”
Section: Methodsmentioning
confidence: 99%
“…2001; Murakami et al. 2007), and plasma BPA levels were lower in hemodialysis patients using polynephron (BPA-free) versus conventional polysulfone dialyzer membranes (Mas et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the metabolism, tissue distribution, and elimination from the body remains unclear and no-TDI has been established for these compounds. Recent studies affirm that OL-HDF could reduce BPA blood levels in dialyzed patients [42,43]. However, the methodology used raises some questions since the number of patients was low, and some issues regarding the analytical method used.…”
Section: Discussionmentioning
confidence: 99%